Wrapping and Unwrapping Material Culture : Archaeological and Anthropological Perspectives. - Harris, Susanna (UNIV COL LONDON INST ARCH PUB., 2014)
This innovative volume challenges contemporary views on material culture by exploring the relationship between wrapping materials and practices and the objects, bodies, and places that define them. Using examples as diverse as baby swaddling, Egyptian mummies, Celtic tombs, lace underwear, textile clothing, and contemporary African silk, the dozen archaeologist and anthropologist contributors show how acts of wrapping and unwrapping are embedded in beliefs and thoughts of a particular time and place. Employing methods of artifact analysis, microscopy, and participant observation, the cont.